Amoana (Orchidaceae, Laeliinae), a new genus and species from Mexico - Leopardi, Carlos; Carnevali, Germán; Romero-González, Gustavo A. (Phytotaxa, 2012)
Encyclia is monophyletic after removal of a number of species to Euchile, Microepidendrum, Oestlundia, and Prosthechea. However, phylogenetic analysis using DNA sequences indicated that Encyclia kienastii belongs to a separate, strongly supported sister group of Alamania, from which it differs markedly in vegetative and floral morphology. Here we transfer Encyclia kienastii to a new genus, Amoana. It is easily distinguished from other genera of Laeliinae by the following combination of characters: pseudobulbs narrowly cylindrical, leaves lanceolate, callus with two conspicuous, divergent, digitiform processes at the base of the midlobe of the labellum, and column reflexed in the middle. We also propose a second species in the genus, Amoana latipetala, which is easy to distinguish from A. kienastii because of its much wider sepals and petals. Amoana is endemic to intermediate elevations in south-central Mexico. A key to the species of the genus is presented. The conservation status of the two species is assessed using the IUCN and MER criteria.